MODULAR TEACHING TECHNOLOGY IN THE HIGHER EDUCATION SYSTEM (British Journal of Global Ecology and Sustainable Development, 2023)
The article "Technology of modular teaching of higher education" provides in-depth information about the concept of modular teaching and its application in the higher education system. It highlights the benefits, challenges, and strategies associated with incorporating modular learning technology into the curriculum. The article recognizes the importance of integrating learning management systems (LMS) and online and blended learning models in supporting modular learning. It also emphasizes flexible learning and gamification to personalize and engage students in a modular learning environment. Overall, the article provides a valuable resource for educators, students, and policy makers seeking to understand and utilize the benefits of modular instructional technology in higher education.